AN INVESTIGATION OF GENDER DIFFERENCES AND SELF-EFFICACY IN WRITING PERFORMANCE AMONG COLLEGE EFL LEARNERS - Masrul, Masrul (ELP (Journal of English Language Pedagogy), 2024)
This study was conducted to examine if gender and self-efficacy affected the writing performance of Indonesian EFL learners in college level. The research sample consisted of 150 students, comprising 67 males and 83 females. The sample was selected using convenience sampling technique, and all participants signed an informed consent form. This correlational study employed statistic analysis to determine the relationships among independent and dependent variables. Statistical analysis involved Pearson correlation test, independent t-test, and hierarchical multiple regression analysis. The results showed that writing performances of male and female groups were significantly different. However, the evidence strengthening the claim that male and female learners perform differently in terms of linguistic aspects of written outcomes was limited. Gender proceeded to explain considerable differences in writing performance, in addition to composition skills.